2001
DOI: 10.1002/1521-3749(200109)627:9<2211::aid-zaac2211>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Arachno-type X56– Zintl Anions in Sr3Sn5, Ba3Sn5, and Ba3Pb5 and Charge Influence on Zintl Clusters

Abstract: Two new binary Zintl phases, Sr 3 Sn 5 and Ba 3 Sn 5 were synthesized and structurally characterized. The revised structure of Ba 3 Pb 5 is also reported. All three compounds are isotypic and crystallize with a modified Pu 3 Pd 5 structure type. The anionic substructure is composed of X 5 6± square pyramidal clusters (X = Sn, Pb), which are described as arachno clusters according to the Wade-Mingos electron counting rules. The electronic structure of the pyramidal Zintl anions and the influence of the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 7 publications
(8 reference statements)
2
48
0
1
Order By: Relevance
“…The stabilization of an orthorhombic UGa 2 metastable phase, probably formed due to kinetic or nucleation reasons, also points to the existence of a range of solubility with the Pu 3 Pd 5 structure type in the uranium-gallium binary system. Several Zintl phases have been previously described as adopting the Pu 3 Pd 5 structure type [15,16]. In the case of UGa 2 it is improbable that it belongs to this family of compounds if it is confirmed that a broad range of homogeneity adopting this Pu 3 Pd 5 structure type exists in the U-Ga system.…”
Section: Atommentioning
confidence: 91%
“…The stabilization of an orthorhombic UGa 2 metastable phase, probably formed due to kinetic or nucleation reasons, also points to the existence of a range of solubility with the Pu 3 Pd 5 structure type in the uranium-gallium binary system. Several Zintl phases have been previously described as adopting the Pu 3 Pd 5 structure type [15,16]. In the case of UGa 2 it is improbable that it belongs to this family of compounds if it is confirmed that a broad range of homogeneity adopting this Pu 3 Pd 5 structure type exists in the U-Ga system.…”
Section: Atommentioning
confidence: 91%
“…The structure solution procedures and the subsequent refinement cycles were performed by means of the SHELXS-97 [9] and the SHELXL-97 [10] programs, respectively. .0446 (1) .0119 (6) .0208 (6) .0179 (5) −.0024 (4) .0168 (3) Sn2 4c 0 .5901 (1) 1/4 .0171 (9) .0195 (8) .0153 (6) 0 .0173 (4) Sn3 4a 0 0 0 .0124 (9) .0232 (9) .0250 (7) .0045 (6) .0202 (4) Metallographic examination was almost impossible so only few tin-richest alloys could be observed.…”
Section: Methodsmentioning
confidence: 99%
“…Five intermediate phases, that is Sr 2 Sn, Sr 5 Sn 3 , SrSn, SrSn 3 , and SrSn 4 , are reported in the diagram, of which only the first three fully characterized. More recent works, mainly of crystallographic type, concerned the following compounds: SrSn 3 , reported as a new trigonal type [5], Sr 3 Sn 5 , crystallizing with a modified Pu 3 Pd 5 -type [6] and the very newly determined SrSn 4 phase [7]. However, some questions like the presumed polymorphism of SrSn and Sr 2 Sn and some aspects of the thermal behaviour of SrSn 3 and SrSn 4 needed to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large excess of In employed in the synthesis, we can speculate that the homogeneity range of this phase is rather small, and that the discussed composition represents the maximum solubility range under these conditions, i.e., BaSn 3-x [19].…”
Section: Resultsmentioning
confidence: 97%